(untitled) (Arquivos em Odontologia, 2016)
Epithelioid angiosarcoma is a rare malignant neoplasm found in vascular endothelial cells. The present study aims to describe the radiological, clinicopathological, and immunohistochemical findings of a case of epithelioid angiosarcoma located in the posterior mediastinum of a 65-year-old male patient who underwent surgery and clinical treatment (Doxorubicin-based chemoterapy). It could be observed that the patient presented poor oral hygiene, severe cervical erosions in his teeth, chronic caries, periodontal disease, and periapical abscess. For this reason, the participation of a dentist in an interdisciplinary team is of utmost importance. Oral support treatment also becomes essential in an attempt to eliminate all foci of oral infections, as well as minimize morbidity and improve the general condition of the patient before, during, and after oncological treatment. In addition, the dentist will work toward the education and motivation of the patient to take on an appropriate oral hygiene so as to minimize the oral complications of chemotherapy, in turn providing better conditions for the patient to eat, speak, socialize, and maintain a high quality of life.